Intrapulmonary Hemorrhage in Small Vessel Vasculitis: A Case Series from Saudi Arabia - Fatima I. Al Beladi; Suzan M. Attar; Afnan M. Samman; Alya A. Filfilan; Haneen A. Ismail; Mariam A. Al-Sheikah (Journal of King Abdulaziz University: Medical Sciences, 2023)
Intrapulmonary hemorrhage is a rare, yet serious condition. The aim was to determine the frequency of Intrapulmonary hemorrhage in small vessel vasculitis and to find out factors associated with low mortality. Retrospective study charts of patients hospitalized at King Abdulaziz University Hospital, Jeddah between January 2000 and December 2010 were reviewed. The review included the underlying diseases, laboratory and radiological investigations, treatment modalities and mortality. Data analysis was performed using the Statistical Package for the Social Sciences. Among 36 patients with small vessel vasculitis were followed up during the ten-year period, six (16.7%) fitted the criteria for intrapulmonary hemorrhage. The underlying diseases were systemic lupus erythematosus (n=2; 33.3%), Goodpastures syndrome (n=1; 16.7%), Wegeners granulomatosis (n=1; 16.7%), and microscopic polyangiitis (n=1; 16.7%); hence, one patient was initially treated as a case of tuberculosis but was later found to have intrapulmonary hemorrhage. The incidence of intrapulmonary hemorrhage in patients with small vessel vasculitis was 16.7%, and the overall mortality rate was 33.3%. Further researches are warranted to explore the relation between mortality and current treatment options and the effect of underlying diseases on the outcome.